NATURE AND CULTURE AS METAPHORS FOR CONCEPTUALIZATION OF THE CONCEPT OF "ECONOMY" (Živi jezici: Journal for Foreign Languages and Literatures, 2017)
In this article, we analyze metaphors in the field of nature and culture used in the German media to conceptualize the abstract concept of "economy". The aim of the author is to find out whether economics is perceived as a natural process that is beyond the reach of man, or as something that man has created through his work. The analysis was done using the methods of cognitive semantics on a corpus of 156 articles published in three leading German media in the midst of the economic crisis of 2008/2009. The aim of the research is to answer the following questions: Do metaphors from the field of nature or culture prevail in the texts? What do these metaphors reveal to us about the notion of economics and participants in the economic process? Based on the empirical analysis, the author comes to the conclusion that the economy in the German public is generally perceived as a natural process and not as a work of man. The economy and its participants are described in vocabulary in the field of wildlife, flora and fauna, hunting and the Darwinian struggle for survival.
Keywords: nature; culture; metaphors; economy